Kesantunan Berbahasa Warganet Indonesia Pada Kolom Komentar Instagram Joko Widodo - Usman Usman; Muhammad Chaidir (Balai Bahasa Sulawesi Selatan, 2025)
The digitalization era has brought significant transformations in Indonesian society's political communication patterns, particularly through Instagram platform which has become a public discussion arena between netizens and political leaders. This research aims to describe the realization of Indonesian netizens' language politeness in Joko Widodo's Instagram comment columns, analyze politeness strategies used, and identify factors influencing politeness variations in digital political communication. The research method uses qualitative approach with library research that is descriptive-analytical, with primary data sources from national and international journal articles from 2020-2024 accessed through Google. The data collection process was carried out using purposive sampling techniques. Data analysis employed content analysis with a thematic approach to identify theoretical patterns and empirical findings related to linguistic politeness in digital communication. The results show that netizens' language politeness is manifested through three main strategies: using linguistic markers such as